Geographic Disparities in Liver Availability: Accidents of Geography, or Consequences of Poor Social Policy?. Issue 9 (5th May 2017) - Ladin, K.; Zhang, G.; Hanto, D. W.
Abstract : Recently, a redistricting proposal intended to equalize Model for End‐stage Liver Disease score at transplant recommended expanding liver sharing to mitigate geographic variation in liver transplantation. Yet, it is unclear whether variation in liver availability is arbitrary and a disparity requiring rectification or reflects differences in access to care. We evaluate the proposal's claim that organ supply is an "accident of geography" by examining the relationship between local organ supply and the uneven landscape of social determinants and policies that contribute to differential death rates across the United States. We show that higher mortality leading to greater availability of organs may in part result from disproportionate risks incurred at the local level. Disparities in public safety laws, health care infrastructure, and public funding may influence the risk of death and subsequent availability of deceased donors. These risk factors are disproportionately prevalent in regions with high organ supply. Policies calling for organ redistribution from high‐supply to low‐supply regions may exacerbate existing social and health inequalities by redistributing the single benefit (greater organ availability) of greater exposure to environmental and contextual risks (e.g. violent death, healthcare scarcity). Variation in liver availability may not be an "accident of geography" but rather a byproduct of disadvantage. Abstract : The authors consider the ethical implications of UNOS's liver redistribution proposal, illustrating that areas facing disproportionate risk may serve as organ reservoirs for safer, healthier, and better‐resourced regions of the country.